2016
DOI: 10.1007/s00441-016-2367-0
|View full text |Cite
|
Sign up to set email alerts
|

A novel culture system for adult porcine intestinal crypts

Abstract: Background Porcine models are useful for investigating therapeutic approaches to short bowel syndrome and potentially to intestinal stem cell (ISC) transplantation. While techniques for the culture and genetic manipulation of ISCs from mice and humans are well established, similar methods for porcine stem cells have not been reported. Methods Jejunal crypts were isolated from murine, human, and juvenile and adult porcine small intestine, suspended in Matrigel, and co-cultured with syngeneic intestinal subepi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
73
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 58 publications
(78 citation statements)
references
References 36 publications
2
73
0
Order By: Relevance
“…Of note, a proper increase of temperatures, such as 39°C or 40°C, can improve the viability of porcine intestinal epithelial cells, which might be related to the relatively high resting physiologic body temperature of pigs. Khalil et al (2016) further found that there was no difference in the expression of differentiation markers between enteroids cultured at 39°C and that cultured at 37°C. Accordingly, exposure to 41°C induced early‐ and late‐phase intestinal cell apoptosis.…”
Section: Discussionmentioning
confidence: 98%
“…Of note, a proper increase of temperatures, such as 39°C or 40°C, can improve the viability of porcine intestinal epithelial cells, which might be related to the relatively high resting physiologic body temperature of pigs. Khalil et al (2016) further found that there was no difference in the expression of differentiation markers between enteroids cultured at 39°C and that cultured at 37°C. Accordingly, exposure to 41°C induced early‐ and late‐phase intestinal cell apoptosis.…”
Section: Discussionmentioning
confidence: 98%
“…27 Optimum culture methods to maintain neonatal and adult porcine enteroids for several weeks have been established, and transplantation of intestinal crypts into the omentum of pigs has resulted in the growth of histologically complete intestine including villi, crypts, lamina propria, nerve elements, and muscularis mucosa. 27,67,68 Methods for cryopreservation and genetic manipulation of porcine enteroids also have been successful, further establishing the porcine enteroid model as a powerful tool for intestinal studies and preclinical assessment. 68 …”
Section: Repair and Regeneration Of Injured Intestine: Insights From mentioning
confidence: 99%
“…27,67,68 Methods for cryopreservation and genetic manipulation of porcine enteroids also have been successful, further establishing the porcine enteroid model as a powerful tool for intestinal studies and preclinical assessment. 68 …”
Section: Repair and Regeneration Of Injured Intestine: Insights From mentioning
confidence: 99%
“…Consequently, pigs represent a candidate species to develop 3D organoids as models for drug screening and other mechanistic translational research (Table ). Gonzalez et al established organoids from whole small intestinal crypts harvested from juvenile pigs (Gonzalez, Williamson, Piedrahita, Blikslager, & Magness, ), and more recently Kahlil et al published a method for the long‐term culture of organoids derived from adult porcine jejunal crypts (Khalil et al, ). To date, the culture of porcine colonic organoid units has not been described in the published literature; therefore, we have successfully developed a method for the long‐term expansion of small intestinal, colonic and rectal organoids derived from adult porcine tissue that can be maintained in a proliferative state for an extended period (Figure c–h).…”
Section: Culture and Establishment Of Porcine Gastrointestinal Organomentioning
confidence: 99%
“…Significant advances in the study of intestinal stem cell physiology have been made using murine models; however, anatomical and physiological differences between rodents and humans limit their translational capacity. As porcine weight, diet and intestinal anatomy is comparable to that of humans (Kararli, 1995), pigs have been extensively used for preclinical studies of intestinal pathophysiology (reviewed in Ziegler, Gonzalez, & Blikslager, 2016 (Khalil et al, 2016). To date, the culture of porcine colonic organoid units has not been described in the published literature; therefore, we have successfully developed a method for the long-term expansion of small intestinal, colonic and rectal organoids derived from adult porcine tissue that can be maintained in a proliferative state for an extended period (Figure 1c-h).…”
Section: Small Intestine and Colonmentioning
confidence: 99%